Convergence of exclusion processes and related phenomena - Ayre, J (2023)
We examine convergence to equilibrium for the facilitated simple exclusion process (FSEP) on the segment with closed boundaries, as well as the symmetric FSEP on the circle. The FSEP on these spaces has degenerate rates, and exhibits transient states which the process will eventually leave to reach an ergodic component if the macroscopic density of particles is at least $1/2$. If the macroscopic density is less than 1/2 the process will hit one of its absorbing states.